2018
DOI: 10.1016/j.puhe.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting antiretroviral therapy adherence among human immunodeficiency virus–positive adolescents in Sub-Saharan Africa: a systematic review

Abstract: Stigma reflects difficult relations between ALHIV and their HIV-negative peers and adults. Most interventions target only those with HIV, suggesting a policy shift towards the wider community could be beneficial. Recommendations include engaging religious leaders and schools to change negative societal attitudes. Limitations of the review include the urban settings and recruitment of predominantly vertically infected participants in most included studies. Therefore, the findings cannot be extrapolated to ALHIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
146
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 81 publications
14
146
1
3
Order By: Relevance
“…In agreement with our review, varieties of studies both in developed and developing countries identified such like variables [6367]. …”
Section: Discussionsupporting
confidence: 89%
“…In agreement with our review, varieties of studies both in developed and developing countries identified such like variables [6367]. …”
Section: Discussionsupporting
confidence: 89%
“…Further, studies in Uganda report serious adherence problems among youth 15-24 years of age [3][4][5][6][7], with barriers including HIV-related stigma, treatment disruptions, caretaker delay in disclosure of HIV status, lack of clinical support [8], and limited access to treatment in rural areas [9]. A systematic review focusing on youth in sub-Saharan Africa (SSA) identified additional barriers to adherence, including treatment side-effects and forgetfulness, while also highlighting facilitators, such as peer and caregiver support as well as knowledge of their own HIV status [10].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative evidence on adolescent HIV and the broader literature on adolescent development suggests that HIV‐related discrimination and internalized shame act as profound barriers to engagement with health services among young people living with HIV [10,15‐16,18,19]. Adolescence is a time when self‐conceptions develop [20].…”
Section: Introductionmentioning
confidence: 99%